2019
DOI: 10.1093/jscr/rjz021
|View full text |Cite
|
Sign up to set email alerts
|

Splenic rupture secondary to amyloid light-chain (AL) amyloidosis associated with multiple myeloma

Abstract: Splenic rupture in the absence of major trauma is a rare occurrence, which may occur by idiopathic means or a specific pathologic process. One such condition, amyloidosis, involves the extracellular deposition of abnormally folded ‘amyloid’ protein, which can affect the spleen. Protein infiltration in the organ may cause splenomegaly and potentially capsular rupture in advanced cases. We describe a 68-year-old male with a history of end-stage renal disease status-post living donor renal transplant on chronic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Furthermore, some patients did not have splenic space-occupying lesions, but the reason for spleen enlargement is not yet clarified. In addition to the involvement of MM cells, this phenomenon could also be due to splenic blood stasis (such as water sodium retention and right heart dysfunction), amyloidosis ( 16 ), other hereditary metabolic cells (Gaucher disease) ( 17 ), and many other unexplained causes of enlarged spleen. In the current study, a total of 84 patients had spleen enlargement; however, there was no significant difference in the detection rate of splenomegaly between the EMM group (26.3%) and the non-EM group (22.7%), rendering it difficult to confirm whether splenomegaly belongs to plasma cell involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some patients did not have splenic space-occupying lesions, but the reason for spleen enlargement is not yet clarified. In addition to the involvement of MM cells, this phenomenon could also be due to splenic blood stasis (such as water sodium retention and right heart dysfunction), amyloidosis ( 16 ), other hereditary metabolic cells (Gaucher disease) ( 17 ), and many other unexplained causes of enlarged spleen. In the current study, a total of 84 patients had spleen enlargement; however, there was no significant difference in the detection rate of splenomegaly between the EMM group (26.3%) and the non-EM group (22.7%), rendering it difficult to confirm whether splenomegaly belongs to plasma cell involvement.…”
Section: Discussionmentioning
confidence: 99%
“…A few reports have indicated that serious symptoms such as fatal GI bleeding and obstruction or perforation sometimes lead to a diagnosis of GI amyloidosis [7][8][9]; however, no previous reports have described intraabdominal bleeding that led to a diagnosis of GI amyloidosis, as in the present case. In some previous reports of patients with systemic amyloidosis, intra-abdominal bleeding developed not because of GI amyloidosis but because of liver or splenic amyloidosis [10][11][12][13]. In addition, to the best of our knowledge, none of these reports indicated that the intra-abdominal bleeding had been caused by TTR amyloid protein.…”
Section: Discussionmentioning
confidence: 94%
“…Atraumatic rupture of the spleen involved by amyloidosis is rare and has been reported in the literature mostly as single cases. [18][19][20] Most of the previously published cases were reported as AL-type (87%), while a small number of AA cases (13%) were also described; with the caveat that these were presumed types based on patient history and/or histochemical/immunohistochemical staining. While atraumatic splenic rupture in our study did indeed occur mostly in patients with AL-amyloid, it also occurred rarely in ALECT2, AA, and AFib amyloid types.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one-third of AL-amyloid spleen specimens were resected due to spontaneous rupture (ie, not associated with trauma). Atraumatic rupture of the spleen involved by amyloidosis is rare and has been reported in the literature mostly as single cases 18–20. Most of the previously published cases were reported as AL-type (87%), while a small number of AA cases (13%) were also described; with the caveat that these were presumed types based on patient history and/or histochemical/immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%